The diurnal variation of bone formation is attenuated in adult patients with type 2 diabetes. Issue 3 (September 2019) - Hygum, Katrine; Starup-Linde, Jakob; Harsløf, Torben; Jørgensen, Niklas Rye; Hartmann, Bolette; Holst, Jens Juul; Langdahl, Bente L
Abstract : Objective: Bone turnover has a diurnal variation influenced by food intake, incretin hormones, the sympathetic nervous system and osteocyte function. The aim of the study was to compare diurnal variation in bone turnover in patients with diabetes and controls. Design: A clinical 24-h study with patients with type 1 diabetes ( n = 5), patients with type 2 diabetes ( n = 5) and controls ( n = 5). Methods: Inclusion criterion: age >50 years. Exclusion criteria: diseases/medication that affect bone metabolism or recent use of incretin-based drugs. We drew blood samples hourly during the day and every 3 h during the night. We served an identical diet on all study days. We used repeated-measures one-way ANOVA to compare the levels of the investigated markers, and we quantified the effect of time by comparing group mean standard deviations. Results: The bone formation marker procollagen type 1 N-terminal propeptide showed a significant interaction between time and group ( P = 0.01), and the mean standard deviation was lower in patients with type 2 diabetes compared with controls ( P = 0.04) and patients with type 1 diabetes ( P = 0.02). Other markers of bone formation and resorption showed significant effect of time. Levels of glucagon-like peptide-2, glucose-dependent insulinotropic peptide and sclerostin only showed significant effect of time (all P values 0.01), but levels of sclerostin tended to being highest in type 2 diabetes and lowest in controls. Conclusions: The diurnal variation in bone formation is attenuated in patients with type 2 diabetes. This is not explained by changes in incretin hormone levels, but possibly mediated by sclerostin.